A review of the North American species of Hemipenthes Loew, 1869 (Diptera: Bombyliidae) - Ávalos-Hernández, Omar (Zootaxa, 2009)
Twenty-three North American species of the genus Hemipenthes Loew are reviewed. Two new species are described (type locality in parentheses): Hemipenthes albus (Mexico, Zacatecas: 25 mi NW Zacatecas), n. sp. and H. translucens (Mexico, Morelos: Quilamula), n. sp. The following synonymies were founded: H. eumenes (Osten Sacken, 1886) is a synonym of H. seminigra Loew, 1869, n. syn.; H. floridiana (Macquart, 1850), H. pima (Painter, 1962), and H. sagata (Loew, 1869 are synonyms of H. celeris (Wiedemann, 1828), n. syns. Evidence presented here shows that H. morio (Linnaeus, 1758) has a Palearctic distribution, not Holarctic as had been considered. Chrysanthrax yaqui (Painter, 1962) is transferred from Villa, n. comb.